Innovative work behaviour: Some psychometric properties of the Lithuanian questionnaire - Geležinytė, Rasa; Bagdžiūnienė, Dalia (Psichologija, 2016)
Employee behaviour which expresses developing, adopting, and implementing new ideas for products and work methods, or, in other words – creates innovations, is especially important for contemporary organisations. Due to innovations, they successfully compete in the market, solve problems inside the organisations, improve work methods, etc. In general, employee innovative work behaviour is crucial for organisational effectiveness and competitive advantage (Van de Ven, 1986; Janssen, Van de Vliert, & West, 2004; Yuan & Woodman, 2010). Innovative behaviour, according to Janssen (2000) is defined as “...the intentional creation, introduction and application of new ideas within a work role, group or organisation, in order to benefit role performance, the group, or the organisation” (p. 288). This type of behaviour is a widely internationally studied phenomenon, several theoretical models of its structure and empirical research instruments are presented in the scientific literature (e.g., Scott & Bruce, 1994; Janssen, 2000; Farr & Tran, 2008; De Jong & Den Hartog, 2010; Messmann & Mulder, 2012). However, studies in Lithuania are at the very preliminary stage and one of the reasons is that there is no adapted reliable and valid instrument. Therefore, the aims of this study were: (1) to develop the Lithuanian multidimensional instrument to measure employee innovative work behaviour and (2) to assess some psychometric characteristics of a new questionnaire. At the first stage of scale development, an integrated approach based on the comprehensive analysis of existing models and methods was used to establish the main forms (dimensions) of innovative work behaviour and items related to every form of innovative behaviour. The list consisting of 92 items was prepared for the further analysis. A part of the items was eliminated after the extensive analysis by experts (psychologists) and a questionnaire consisting of 29 items was finalized for this empirical study. To evaluate the validity of the questionnaire, the following scales were also included in the study: initiative (Frese, Kring, Soose, & Zempel, 1996), pro-change behaviours (Giangreco & Peccei, 2005), routine seeking and short-term thinking (Oreg, 2003), pessimism (Wanous, Reichers, & Austin, 2000) and also the widely used unidimensional Scott & Bruce (1994) innovative behaviour scale. A cross-sectional study was carried out in the sample of 283 employees from Lithuanian state and business organisations. The participants’ average age was 34 years, the majority (84 %) had university education, 75 % were women, the average tenure was 6 years, 77 % were working in the subordinate’s position and 56 % were from business organisations. The results of the study have revealed that the Lithuanian Innovative Work Behaviour Questionnaire (LIWBQ) has a high internal reliability (Cronbach α = 0.938) and consists of five factors that were extracted using the exploratory factor analysis: Interest in innovations, Idea exploration and generation, Idea testing and evaluation, Idea promotion, and Idea implementation. The scales’ Cronbach α varies from 0.744 to 0.892. The validity of the instrument was confirmed by positive inter-correlations (p < 0.01) between the LIWBQ and its dimensions and similar constructs (initiative and pro-change behaviours) and also negative correlations with constructs of the opposite meaning: routine seeking, short-term thinking and pessimism. Scores of all dimensions and the whole score also positively correlated with the Scott & Bruce (1994) innovative behaviour scale. Based on the results of exploratory factor analysis and correlations, the construct, convergent and discriminant validity of LIWBQ and its five dimensions were confirmed. In conclusion, it could be stated that Lithuanian Innovative Work Behaviour Questionnaire is a new research tool which meets the main requirements of validity and reliability for the use in research and practice and for further research. Study limitations, directions for the future research and practical implications are discussed.
Keywords: innovative work behaviour; questionnaire; reliability; validity; employees